(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
There are various methods of teaching English. When teaching a foreign language, it is necessary to pay attention to new ways of stimulating students’ speech. The article discusses non-traditional methods of grammatical, structural and communicative and teaching of foreign languages.